International organizations and global civil society : histories of the Union of International Associations - Laqua, Daniel; van Acker, Wouter; Verbruggen, Christophe (London: Bloomsbury Academic, 2019)
"Edited by Daniel Laqua, Wouter Van Acker and Christophe Verbruggen"